2010
DOI: 10.1037/a0018438
|View full text |Cite
|
Sign up to set email alerts
|

Examining the protective effects of mindfulness training on working memory capacity and affective experience.

Abstract: We investigated the impact of mindfulness training (MT) on working memory capacity (WMC) and affective experience. WMC is used in managing cognitive demands and regulating emotions. Yet, persistent and intensive demands, such as those experienced during high-stress intervals, may deplete WMC and lead to cognitive failures and emotional disturbances. We hypothesized that MT may mitigate these deleterious effects by bolstering WMC. We recruited 2 military cohorts during the high-stress predeployment interval and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
543
2
18

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 733 publications
(599 citation statements)
references
References 83 publications
36
543
2
18
Order By: Relevance
“…Mindfulness is a state of mind that decreases avoidance and rumination and increases working memory resources. Thus, the increase in specificity following mindfulness training can be explained in terms of a reduction in functional avoidance, capture and rumination, and an increase in executive control (Hargus et al 2010;Heeren et al 2009;Jha, Stanley, Kiyonaga, Wong and Gelfand 2010). This is the first study to investigate whether there is an association between trait mindfulness and memory specificity.…”
mentioning
confidence: 91%
“…Mindfulness is a state of mind that decreases avoidance and rumination and increases working memory resources. Thus, the increase in specificity following mindfulness training can be explained in terms of a reduction in functional avoidance, capture and rumination, and an increase in executive control (Hargus et al 2010;Heeren et al 2009;Jha, Stanley, Kiyonaga, Wong and Gelfand 2010). This is the first study to investigate whether there is an association between trait mindfulness and memory specificity.…”
mentioning
confidence: 91%
“…It is currently an open empirical question as to what specific benefits-if any-are observed after a specific duration of a specific style of mindfulness meditation training using a well-controlled study design (Van Dam et al 2017). Studies with only one session of mindfulness training have shown no cognitive benefits (Banks et al 2015;Johnson et al 2015) whereas studies with longer duration mindfulness training (e.g., 2 to 8 weeks) have shown more robust cognitive benefits (Jha et al 2010(Jha et al , 2017Mrazek et al 2013). As the current study is the first to test the benefits of focused attention mindfulness meditation training on working memory capacity using recommended rigorous criteria (Shipstead et al 2012a, b), observation of any benefit following mindfulness training in the current study can inform future research.…”
Section: Resultsmentioning
confidence: 99%
“…Mindfulness meditation has also been shown to buffer and protect working memory capacity and working memory performance from decrements due to stress (Jha et al 2010(Jha et al , 2017 and negative affect (Banks et al 2015). While promising, these studies all lacked one or more of the following design criteria: random assignment; comparison to active, adaptive controls; or using multiple, valid measures of working memory capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations